1994
DOI: 10.1037/0022-0167.41.2.155
|View full text |Cite
|
Sign up to set email alerts
|

Counselor content orientation, counselor race, and Black women's cultural mistrust and self-disclosures.

Abstract: Black women were exposed to Black or White female counselors who used verbal statements reflective of either a cultural or a universal content orientation. The effects of counselor content orientation, counselor race, and participants' cultural mistrust levels on the frequency and depth of participant self-disclosures, ratings of counselor credibility, and willingness to self-refer were examined. Counselor content orientation related significantly to depth of disclosure and willingness to self-refer, with part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
100
2

Year Published

1999
1999
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(106 citation statements)
references
References 33 publications
4
100
2
Order By: Relevance
“…[19][20][21] Higher levels of cultural mistrust among African Americans have also been found to contribute to more negative views and expectations of psychotherapy. [22][23][24][25][26][27][28] An assessment of the role of mistrust in the government and medical care among an HIV-infected population found more positive health outcomes among individuals who had higher levels of trust in their health care providers. Specifically, mistrust was found to be a barrier to service use, and therefore, those with higher levels of mistrust in their health care providers had lower levels of physical and mental health, more emergency room visits, and less likely to take their medications.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21] Higher levels of cultural mistrust among African Americans have also been found to contribute to more negative views and expectations of psychotherapy. [22][23][24][25][26][27][28] An assessment of the role of mistrust in the government and medical care among an HIV-infected population found more positive health outcomes among individuals who had higher levels of trust in their health care providers. Specifically, mistrust was found to be a barrier to service use, and therefore, those with higher levels of mistrust in their health care providers had lower levels of physical and mental health, more emergency room visits, and less likely to take their medications.…”
Section: Introductionmentioning
confidence: 99%
“…Although the effect of color-blind racial attitudes on the therapeutic process has not been directly studied, research evidence from client reports suggests that counselors who were culturally responsive (perhaps a reflection of the degree to which a therapist is color-blind) were rated as more credible and culturally competent (Atkinson, Casas, & Abreu, 1992;Gim, Atkinson, & Kim, 1991;Pomales, Claiborn, & LaFromboise, 1986), reported higher client satisfaction and lower client attrition rates from counseling (Wade & Bernstein, 1991), and had clients who self-disclosed more intimately (Thompson, Worthington, & Atkinson, 1994) than did counselors who were culturally unresponsive. Furthermore, Thompson and Jenal (1994) found that African American women became more frustrated and exasperated with counselors, regardless of their racial background (i.e., African American, European American), when the counselors actively avoided racial content in counseling.…”
mentioning
confidence: 99%
“….") (Thompson, Worthington, & Atkinson, 1994). In another condition, subjects were interviewed by counselors who used a more universal approach ("As a freshman at this school, you have .…”
Section: Need To Acknowledge Cultural Mistrustmentioning
confidence: 99%